2011
DOI: 10.1002/anie.201008004
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Crystal Engineering of Zinc‐Substituted Myoglobin to Construct a Long‐Lived Photoinduced Charge‐Separation System

Abstract: Photoinduced electron transfer (ET) in native photosynthesis reactions is efficiently achieved by the accumulation of different types of redox cofactors within protein assemblies immobilized in cell membranes. [1][2][3] The precise arrangement of each cofactor in the molecular spaces enables them to retain the long-lived charge-separated state, which promotes multistep reactions in biological systems. To elucidate the mechanism of the biological ET reactions and to develop light energy conversion systems, arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 33 publications
3
62
0
Order By: Relevance
“…These crystals are able to capture and deposit metal ions and metal complexes within solvent channels when the crystals are soaked in the solutions containing the metal ions because the amino acid side chains responsible for coordinating the metal ions are periodically aligned on the surface of solvent channels of the crystal lattices 17–22. We have demonstrated the accumulation of functional molecules such as metal complexes and metal clusters into the solvent channels of porous myoglobin crystals by chemical conjugation and coordination interactions 23, 24. With respect to inorganic materials, it has been reported that protein crystals can serve as nanoreactors for the preparation of nanoparticles 25, 26.…”
Section: Characteristics Of the Copt‐nps Prepared In The Hewl Crystalmentioning
confidence: 94%
“…These crystals are able to capture and deposit metal ions and metal complexes within solvent channels when the crystals are soaked in the solutions containing the metal ions because the amino acid side chains responsible for coordinating the metal ions are periodically aligned on the surface of solvent channels of the crystal lattices 17–22. We have demonstrated the accumulation of functional molecules such as metal complexes and metal clusters into the solvent channels of porous myoglobin crystals by chemical conjugation and coordination interactions 23, 24. With respect to inorganic materials, it has been reported that protein crystals can serve as nanoreactors for the preparation of nanoparticles 25, 26.…”
Section: Characteristics Of the Copt‐nps Prepared In The Hewl Crystalmentioning
confidence: 94%
“…Koshiyama and co‐workers constructed an artificial long‐lived photo‐induced charge‐separation system using a single myoglobin (from sperm whale) crystal with different redox cofactors fixed in defined locations . Methyl viologen (MV) mediated the electron transfer between Zn porphyrin (ZnP, electron donor) and an oxo‐centered triruthenium cluster (Ru 3 O), electron acceptor) in the crystal.…”
Section: Chemoenzymatic Cascade Reactionsmentioning
confidence: 99%
“…[7a] After extracting its heme using a slightly modified method from the literature (see the SI), [10] the protein was reconstituted with ZnPP (Figure 1). The UV-vis spectrum of ZnPP-reconstituted protein, ZnPPFe B Mb1, has absorption peaks at 427 nm, 553 nm, and 595 nm (Figure 2).…”
mentioning
confidence: 99%